(untitled) (Research, Society and Development, 2021)
Objective: The purpose in this in vitro study was to evaluate the influence of gamma irradiation on the marginal integrity and surface morphology of bulk fill resin composites by Microcomputed tomography (μ-CT) and Scanning Electron Microscopy (SEM). Methods: class I cavities (3 mm deep) were prepared in 60 third molars restored with the following resin composites: Filtek™ Bulk Fill (FBF), TetricEvoCeram Bulk Fill (TBF), X-tra Fil Bulk Fill (XTA) and Filtek™ Z350 (Z350) (n = 15). The samples were immersed in 50% silver nitrate solution, scanned and subdivided according to the gamma radiation doses (Control group – no radiation, 30 and 60 Gy). After irradiation, the teeth were again immersed in silver nitrate and scanned. For morphological analysis, 12 cylindrical (10 x 2mm) specimens were and submitted to the studied radiation regimens (n =4). Data were analyzed by the Kruskal-Wallis and Fisher LSD tests (α = 0.05). Results: it was observed that the irradiation negatively affected the marginal integrity of samples restored with FBF (p < 0.05). No significant differences were observed for the other resin composites. No changes were shown in the surface morphology of bulk fill composites, despite irradiation having affected the surface morphology of the control group (Z350). It was concluded that the accumulated doses of 30 and 60 Gy negatively affected the tooth-restoration interface of FBF and at the surface morphology of Z350. Conclusions: TetricEvoCeram, and X-tra Fil Bulk Fill resin composites can be considered alternatives in the restorative treatment of patients submitted to radiotherapy of the head and neck.